Proceedings of the 1st Workshop on NLP for COVID-19 (Part 2) at EMNLP 2020 2020
DOI: 10.18653/v1/2020.nlpcovid19-2.24
|View full text |Cite
|
Sign up to set email alerts
|

Tracking And Understanding Public Reaction During COVID-19: Saudi Arabia As A Use Case

Abstract: The coronavirus disease of 2019 (COVID-19) has a huge impact on economies and societies around the world. While governments are taking extreme measures to reduce the spread of the virus, people are getting affected by these new measures. With restrictions like lockdown and social distancing, it became important to understand the emotional response of the public towards the pandemic. In this paper, we study the reaction of Saudi Arabia citizens towards the pandemic. We utilize a collection of Arabic tweets that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Few approaches have been proposed for sentiment analysis of Arabic COVID-19 tweets [9,42,43]. Two of these approaches employed classical machine learning algorithms to classify the tweets into positive, negative, and neutral sentiments [42,43].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Few approaches have been proposed for sentiment analysis of Arabic COVID-19 tweets [9,42,43]. Two of these approaches employed classical machine learning algorithms to classify the tweets into positive, negative, and neutral sentiments [42,43].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Few approaches have been proposed for sentiment analysis of Arabic COVID-19 tweets [9,42,43]. Two of these approaches employed classical machine learning algorithms to classify the tweets into positive, negative, and neutral sentiments [42,43]. Aljameel et al [42] trained their model on 10,623 tweets labeled manually with positive, negative, and neutral sentiments and an F1-score of 0.84 was reported using SVM with Bigram term frequencyinverse document frequency (TF-IDF).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they only included statistical analysis and clustering to generate summaries with some suggestion of future work. Yet, there are some studies with specific goals, such as analysis of the reaction of citizens during a pandemic [ 21 ] and identification of the most frequent unigrams, bigrams, and trigrams of tweets related to COVID-19 [ 22 ]. In addition, considering the study by Alanazi et al [ 23 ] that identified the symptoms of COVID-19 from Arabic tweets, the authors noted the limitation that they used modern standard Arabic keywords only, and it would be important to consider dialectical keywords in order to better catch tweets on COVID-19 symptoms written in Arabic, because some Arab users post on social media in their own local dialect.…”
Section: Introductionmentioning
confidence: 99%
“…However, this effect began to decline over time. A recent study showed how people supported each other during the pandemic through social media by raising trendy hashtags on the Twitter platform [ 13 ]. Furthermore, the Saudi government designated March 2 of every year as "Health Martyr Day" as a sign of solidarity and appreciation to all healthcare workers who have lost their lives on the frontline against COVID-19 [ 14 ].…”
Section: Introductionmentioning
confidence: 99%